Hubungan Response Time Perawat Dengan Tingkat Kepuasan Pada Pasien Kategori Australian Triage Scale (ATS) 3 Terhadap Nyeri Di IGD Rumah Sakit Kanker Dharmais - Alif Wisageni; Yuni Susilowati; Ria Setia Sari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Introduction: The Emergency Room (IGD) is the first stop and referral place for patients. Patient visits to the emergency room (ER) continue to increase every year. Dharmais Cancer Hospital 66.46% are Australian Triage Scale (ATS) 3 category patients with pain. The nurse's actions in caring for patients must act quickly and sort patients according to priority. Response time is an indicator of success in treating emergency department (ER) patients. Objective: to determine the relationship between nurse response time and satisfaction level in Australian Triage Scale (ATS) 3 category patients with pain in the emergency department of Dharmais Cancer Hospital. Research Method: quantitative analysis with cross sectional design. The sample size of this study was 132 using a purposive sampling technique. Data analysis using Chi Square Test. Research results: most of the nurse's response time is fast as much as 76.5%, the satisfactory level of satisfaction is as much as 64.4%. There is a relationship between nurse response time and the level of satisfaction in patients in the Australian Triage Scale (ATS) 3 category with pain in the emergency room at Dharmais Cancer Hospital with p = 0.001. Conclusion: There is a relationship between the response time of nurses and the level of satisfaction in patients with the Australian Triage Scale (ATS) 3 category with pain. Research suggestion: It is expected that nurses maintain a fast response time of ≤ 5 minutes and are in accordance with the SPO, besides that it is hoped that nurses can manage their psychology because of high motivation and hard work of nurses in carrying out their responsibilities making nurse performance better, proper handling so that services patients to be effective and efficient.